Comparison of gamma and electron beam irradiation for using phyto-sanitary treatment and improving physico-chemical quality of dried apricot and quince. Issue 1 (January 2019) - Rather, Sarver A.; Hussain, Peerzada R.; Suradkar, Prashant P.; Ayob, Omeera; Sanyal, Bhaskar; Tillu, Abhijit; Chaudhary, Nishant; Chavan, R.B.; Ghosh, Sunil K.
ABSTRACT: The present study was conducted to compare the effect of gamma and electron beam irradiation for use a phyto-sanitary treatment and improving the physico-chemical and antioxidant activity of dried apricot and quince irradiated at doses of 1, 2, 3, and 4 kGy. Results of the present study revealed that both gamma and electron beam irradiation were significantly ( p ≤ 0.05) effective in maintaining the physico-chemical quality and enhancing the antioxidant potential of dried apricot and quince. The ΔE* ab values indicated that there was no significant ( p ≤ 0.05) noticeable difference induced in color of the dried apricot and quince by the two methods of irradiation. Textural parameters (hardness, chewiness, gumminess) recorded decreasing trend with irradiation particularly at doses beyond 2.0 kGy under both the methods of irradiation. Strong inverse correlation ( r = –0.85) existed between gamma irradiation and rehydration ratio whereas moderate inverse correlation ( r = –0.73) existed between rehydration ratio and electron beam irradiation for both the products. Both gamma and electron beam irradiation at 3.0 and 4.0 kGy proved effective in reducing the number of viable microorganisms to below detection limits in both the products. In dried apricots treated with 4.0 kGy of gamma irradiation, the increase in fructose, glucose, and sucrose content over control was of the order of 10.6% and 25.7% compared to 8.9%, 7.8% and 17.5% for same dose of electron beam irradiation. Dried quince treated with gamma and electron beam irradiation at 4.0 kGy recorded an enhancement in fructose, glucose, and sucrose contents of the order of 14.8%, 15.5%, 30.1% and 11.2%, 14.2%, 27.2%, respectively. The results of the antioxidant activity revealed significant ( p ≤ 0.05) decrease in EC50 values and corresponding increase in antioxidant activity of dried apricot and quince due to gamma and electron beam irradiation.